Bagasse pith as a fish pond input - Circa, Antonio V.; Edwards, Peter; Wee, Kok Leong; Lin, Chang Kwei; US - ASEAN (Bangkok : Asian Institute of Technology, 1987)
The aim of this study was to determine the feasibility of utilizing bagasse pith (sieved bagasse ) as a fish pond input through nutrient supplementation. The treatments involved four bagasse loadings (0, 50, 100, 150 kg dry matter/ha/day) and four nitrogen a nd phosphorus supplementation rates with a 10:1 ratio of nitrogen to phosphorus ( 0:0, 2:0.2, 4:0.4, 6 kg nitrogen: 0 .6 kg phosphorus (as P205 ) / ha/day ) . Poor fish yields were obtained inspite of high survival rates in treatments with bagasse alone at all loading rates. The highest net extrapolated yield from these treatments of 505 kg/ha/yr was obtained with the 10 0 kg dry matte r/ha/day loading. Treatments with nitrogen and phosphorus a lone incurred early total fish mortality at the medium and highest rates, possibly due to rise in pH. Yields with nutrient-supplemented bagasse demon started promising results with net extrapolated yields of 2030, 1969 , 1968, 1947, a nd 1933 kg/ha/yr from the 150 and 4: 0.4, JOO and 2:0.2 , 100 and 4:0.4 , 150 and 2:0.2 and 100 kg dry matter bagasse/ ha/day and 6 kg nitrogen:0.6 kg phosphorus/ha/day treatments, respectively. Survival rates in these treatments ranged from 90-1 00%. Water quality in all bagasse loadings deteriorated with time regardless of nitrogen a nd phosphorus supplementation l eve ls and at an increasing rate as the loading was increased. The 1 00 kg dry matter/ ha/day loading gave t h e best yields compare d to other loading s , at all l eve l s of nutrient supplementation, while the 2 legnitrogen:0. 2 kg phosphorus/ha/day supplementation gave the best results compared to other nutrient l eve l s at all bagasse loadings. The optimum bagasse dry matter loading and nutrient supplementation rates at steady-state conditions ranged from 50-100 kg dry matter bagasse/ha/day a nd 2:0.2-4 kg : 0 .4 kg phosphorus/ha/day.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1987
Keywords: Waste products as feed; Fish-culture; Bagasse